MODEL OF FORMATION OF OPTIMAL MOTIVATION OF STUDENTS OF NON-LANGUAGE UNIVERSITY IN THE PROCESS OF FOREIGN LANGUAGE STUDY - Ridel Т. М. (Pedagogy of Higher and Secondary Education, 2022)
The paper filed characteristic constituent units forming the optimal model of motivation teaching students non-linguistics higher educational establishments in the process of learning a foreign language. Proved that the optimality criterion of the model is formedness motives, the motives that are ... relatedto the activities of mastering a foreign language and the process of its occurrence.